Multi-organ failure after acute kidney injury in patient with HIV and COVID-19. (September 2020) - Elhadi, M.; Momen, A.A.; Abdulhadi, O.M.A.S.; Msherghi, A.
Abstract: We describe the first death in Libya from coronavirus disease 2019 (COVID-19) presenting as acute kidney failure in an 86-year-old woman in Tripoli with no recent travel history. She had a history of type 2 diabetes mellitus and human immunodeficiency virus (HIV) infection, for which she reported non-compliance with treatment. On 15 March 2020, she was diagnosed with lobar pneumonia and her condition did not improve. On 30 March she presented to Tripoli University Hospital Emergency Department with a cough, temperature of 39°C, respiratory rate of 24 breaths/min, pulse of 110 beats/min and blood pressure of 130/80 mmHg. Nasopharyngeal swab and sputum were negative for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) on real-time RT-PCR. On 1 April 2020, the patient's status deteriorated and she was diagnosed with acute kidney injury as a complication of sepsis, with a urea level of 240 mg/dL (reference range 5–50 mg/dL) and creatinine level of 7.69 mg/dL (reference range 0.4–1.3 mg/dL). She was referred for dialysis at Tripoli University Hospital on 2 April. However, the patient died, despite attempted resuscitation, from multiple organ dysfunction syndrome following acute kidney injury. A nasopharyngeal swab and sputum were collected, which were positive for SARS-CoV-2 on real-time RT-PCR. This case provides an insight into the importance of testing for SARS-CoV-2, in the context of an epidemic in all patients with atypical presentation, particularly those with associated HIV infection. Highlights: We present the first case of death due to COVID-19 in Libya. Relying on RT-PCR for diagnosis of COVID-19 carry high risk due to delay in initiation of treatment. Acute kidney injury can be precipitated by COVID-19. Civil war and fragility of health care system in Libya are ongoing obstacles for management and control of COVID-19. COVID-19 demonstrate high challenge for low-middle income countries with limited resources.